A wear-resistant coating and preparation method thereof

By using raw materials such as resin prepolymer emulsion, modified nanospherical alumina and polyether ether ketone microspheres in aqueous acrylic coatings, the coating with a cross-linked network structure is solved, and the existing coatings are not wear-resistant under extreme working conditions are achieved, and higher wear resistance and mechanical properties are achieved.

CN119019903BActive Publication Date: 2025-04-04无锡市造漆厂有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411286093.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-04-04
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing water-based acrylic coatings have problems such as low wear resistance under extreme working conditions, which are difficult to meet higher wear resistance and mechanical properties requirements.

Method used

Raw materials such as resin prepolymer emulsion, modified nanospherical alumina and polyether ether ketone microspheres are used to construct coatings with cross-linked network structures through photoinduced graft polymerization, thereby improving the wear resistance of the coating.

Benefits of technology

It significantly improves the wear resistance and mechanical properties of the coating, enhances the impact resistance and lubrication properties of the coating, and shortens the coating curing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043145470000031
    Figure BDA0005043145470000031
  • Figure BDA0005043145470000081
    Figure BDA0005043145470000081
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and specifically relates to a wear-resistant coating and a preparation method thereof; the wear-resistant coating is made of the following raw materials, by mass: 40-50 parts of resin prepolymer emulsion, 6-11 parts of modified nano-spherical alumina, 5-10 parts of polyetheretherketone microspheres, 0.01-0.03 parts of stearic acid, and 0.03-0.05 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide. In the wear-resistant coating prepared by the present invention, the polyetheretherketone microspheres can increase the wear resistance of the coating, the resin prepolymer emulsion serves as a flexible part, and the modified nano-spherical alumina serves as a coating lubricating part; the three are photo-initiated graft polymerization, and the cross-linked network structure constructed has a certain stability, and the prepared wear-resistant coating has high wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a wear-resistant coating and a preparation method thereof. Background Art

[0002] Water-based paint is widely used due to its advantages of environmental protection and little harm to human body. Water-based paint can be mainly divided into water-based acrylic paint, water-based epoxy paint, water-based alkyd paint and water-based polyurethane paint according to the type of resin. Among them, water-based acrylic paint is an acrylic resin paint with acrylic polymer synthesized from methacrylate, acrylate and vinyl monomers as the base material and water as the dispersant. It has good stability and adhesion and low cost; however, traditional water-based acrylic paint has many shortcomings, and the performance of the coating is often improved by introducing some functional monomers or modified materials.

[0003] For coatings, wear resistance is a more important indicator. Li Minghua et al. (Li Minghua, Green physically modified nano-silica and anti-scratch performance of composite coatings, China Powder Technology, 2022) prepared a physically modified water-based nano-silica dispersion by ultrasonic dispersion, and then added it to water-based acrylic coatings. The contact angle of the prepared nano-composite water-based coating with water increased from 94.3° to 105.1°, the wear resistance of the coating increased from less than 5 to 10, and the anti-scratch load increased from 0.94kg to 2.15kg, without affecting the gloss and transparency of the coating.

[0004] Under some extremely harsh working conditions, the requirements for solid wear-resistant coatings are constantly increasing, and the coatings are required to have better wear resistance and mechanical properties. Summary of the invention

[0005] The wear-resistant coating in the prior art has the problem of low wear resistance. In order to solve this problem, the present invention provides a wear-resistant coating and a preparation method thereof.

[0006] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a wear-resistant coating, wherein the wear-resistant coating is made of the following raw materials, in parts by mass:

[0008] 40-50 parts of resin prepolymer emulsion, 6-11 parts of modified nano spherical alumina, 5-10 parts of polyetheretherketone microspheres, 0.01-0.03 parts of stearic acid, and 0.03-0.05 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0009] Preferably, the resin prepolymer emulsion comprises the following preparation steps:

[0010] Allyl methacrylate and butyl acrylate are dissolved in toluene, sodium dodecyl sulfate is added, t-BuP4 and benzoyl peroxide are added under anaerobic conditions, and the reaction is carried out at 35-45° C. for 2-3 hours, and then a terminator is added to terminate the reaction to obtain a resin prepolymer emulsion.

[0011] Preferably, in terms of mass ratio, allyl methacrylate:butyl acrylate:toluene=4-5:1:25-28; in terms of mass ratio, t-BuP4:benzoyl peroxide=1:0.4-0.7; the t-BuP4 accounts for 1.5%-1.8% of the total mass of the allyl methacrylate and the butyl acrylate.

[0012] Preferably, the terminator is a mixed solution of hydroquinone and toluene.

[0013] Preferably, the modified nano-spherical alumina comprises the following preparation steps:

[0014] Dissolve silane coupling agent KH590 in anhydrous ethanol, adjust the pH value to 3-4, and react at 35-40°C for 30-40 minutes to obtain liquid A;

[0015] Add nano-spherical alumina into liquid A, react for 2-3 hours, wash, filter and dry to obtain modified nano-spherical alumina.

[0016] Preferably, in terms of mass ratio, nano-spherical alumina: A liquid = 1:20-25.

[0017] Preferably, the polyetheretherketone microspheres include the following preparation steps:

[0018] Add polyetheretherketone powder into concentrated sulfuric acid and stir at 45-50°C for 8-10 hours to obtain liquid B; mix deionized water and ethanol to obtain liquid C;

[0019] Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 3-4 hours, then allowed to stand for 8-10 hours, centrifuged and washed, and then hydrothermally reacted at 155-165° C. for 8-10 hours to obtain polyetheretherketone microspheres.

[0020] Preferably, polyetheretherketone powder: concentrated sulfuric acid = 1 g: 8-12 mL.

[0021] Preferably, the polyetheretherketone powder has a particle size of 600-1000 mesh; if the particle size is too large, it is easy to separate from the system, affecting compatibility.

[0022] Preferably, the liquid C also includes sodium dodecyl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate, and the mass ratio of sodium dodecyl sulfate to sodium polyoxyethylene fatty alcohol ether sulfate is 1:1.5-2.

[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned wear-resistant coating, which is specifically as follows:

[0024] The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid are mixed, and then 2,4,6-trimethylbenzoyldiphenylphosphine oxide is added, and the mixture is stirred for 15-20 minutes under anaerobic conditions to obtain a wear-resistant coating.

[0025] The high specific surface area of ​​nano-spherical alumina leads to large surface energy and surface tension. In the coating, these highly surface-active nanoparticles are easily attracted to each other and agglomerated to form larger particle clusters. This agglomeration phenomenon will seriously affect the dispersibility and stability of nano-spherical alumina in the coating. There is also a strong van der Waals force between the atoms or molecules on the surface of nano-spherical alumina, which causes the nanoparticles to gather together in the coating, further aggravating the agglomeration phenomenon. Therefore, silane coupling agent KH590 is used to modify nano-spherical alumina and introduce a thiol structure; at the same time, t-BuP4 is used to catalyze benzoyl peroxide to initiate the copolymerization of allyl methacrylate and butyl acrylate, retaining the double bond structure, so that it is convenient for it to form a stable bonding structure with the modified nano-spherical alumina.

[0026]

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The polyetheretherketone microspheres prepared by the present invention have certain reactivity when the ketone group is converted into a hydroxyl structure under the action of ultraviolet light, and have both coating wear resistance enhancement and photoinitiator properties; when subjected to external friction, the polyetheretherketone microspheres can resist deformation caused by external forces; during the coating compounding process, the polyetheretherketone has a benzophenone-like structure, which can promote the cross-linking with the resin body and the reaction speed of the modified nano-spherical alumina and the thiol-double bond bonding of the resin prepolymer emulsion, thereby shortening the coating curing time;

[0029] (2) The uniform distribution of the modified nano-spherical alumina prepared by the present invention can fill the tiny pores and defects in the coating, making the coating surface smoother and reducing friction resistance and wear; in addition, the smooth coating surface can also provide better fluidity and sliding properties, thereby improving the lubrication properties of the coating;

[0030] (3) In the wear-resistant coating prepared by the present invention, polyetheretherketone microspheres can increase the wear resistance of the coating, the resin prepolymer emulsion serves as the flexible part, and the modified nano-spherical alumina serves as the lubricating part of the coating; the three are photo-initiated graft polymerization to construct a cross-linked network with a certain stability, and the prepared wear-resistant coating has high wear resistance. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is explained in detail below with reference to several representative embodiments of the present invention.

[0032] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0033] Example 1

[0034] A wear-resistant coating, the wear-resistant coating is made of the following raw materials, measured by mass:

[0035] 45 parts of resin prepolymer emulsion, 10 parts of modified nano-spherical alumina, 7 parts of polyetheretherketone microspheres, 0.02 parts of stearic acid, and 0.03 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide;

[0036] The preparation method of the wear-resistant coating is as follows:

[0037] (1) Preparation of resin prepolymer emulsion

[0038] 5.12 g of allyl methacrylate and 1.28 g of butyl acrylate were dissolved in 33.5 g of toluene, 0.03 g of sodium dodecyl sulfate was added, nitrogen was continuously introduced into the device, and then 0.1 g of t-BuP4 and 0.05 g of benzoyl peroxide were added. After reacting at 35° C. for 3 h, a mixed solution of hydroquinone and toluene (hydroquinone: toluene=1:10, n / n) was added to terminate the reaction to obtain a resin prepolymer emulsion;

[0039] (2) Preparation of modified nano-spherical alumina

[0040] Dissolve 0.5g of silane coupling agent KH590 in 25g of anhydrous ethanol, adjust the pH value to 3 with 0.5mol / L hydrochloric acid, and react at 35℃ for 40min to obtain liquid A;

[0041] 3.06 g of nano-spherical alumina was added to 61.2 g of liquid A, and the mixture was reacted for 2 h, and then washed with anhydrous ethanol, filtered, and dried to obtain modified nano-spherical alumina;

[0042] (3) Preparation of polyetheretherketone microspheres

[0043] Add 3.28g 600-mesh polyetheretherketone powder to 26.24mL concentrated sulfuric acid and stir at 45°C for 8h to obtain liquid B; mix 754.4g deionized water, 65.6g anhydrous ethanol, 0.06g sodium dodecyl sulfate and 0.09g sodium polyoxyethylene fatty alcohol sulfate to obtain liquid C;

[0044] Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 3 h, then allowed to stand for 10 h, centrifuged and washed, and then subjected to hydrothermal reaction at 155 °C for 9 h to obtain polyetheretherketone microspheres;

[0045] (4) Preparation of wear-resistant coating

[0046] The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid were mixed, 2,4,6-trimethylbenzoyldiphenylphosphine oxide was added, nitrogen was introduced and stirred for 15 minutes to obtain the wear-resistant coating.

[0047] Example 2

[0048] A wear-resistant coating, the wear-resistant coating is made of the following raw materials, measured by mass:

[0049] 40 parts of resin prepolymer emulsion, 7 parts of modified nano-spherical alumina, 8 parts of polyetheretherketone microspheres, 0.02 parts of stearic acid, and 0.03 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide;

[0050] The preparation method of the wear-resistant coating is as follows:

[0051] (1) Preparation of resin prepolymer emulsion

[0052] 6.4 g of allyl methacrylate and 1.28 g of butyl acrylate were dissolved in 33.5 g of toluene, 0.05 g of sodium dodecyl sulfate was added, nitrogen was continuously introduced into the device, and then 0.13 g of t-BuP4 and 0.06 g of benzoyl peroxide were added. After reacting at 40° C. for 2 h, a mixed solution of hydroquinone and toluene (hydroquinone: toluene=1:10, n / n) was added to terminate the reaction to obtain a resin prepolymer emulsion;

[0053] (2) Preparation of modified nano-spherical alumina

[0054] Dissolve 0.5g of silane coupling agent KH590 in 27.5g of anhydrous ethanol, adjust the pH value to 3 with 0.5mol / L hydrochloric acid, and react at 35℃ for 35min to obtain liquid A;

[0055] 3.06 g of nano-spherical alumina was added to 76.5 g of liquid A, and the mixture was reacted for 3 h, and then washed with anhydrous ethanol, filtered, and dried to obtain modified nano-spherical alumina;

[0056] (3) Preparation of polyetheretherketone microspheres

[0057] Add 3.28g 700-mesh polyetheretherketone powder into 32.8mL concentrated sulfuric acid and stir at 50°C for 8h to obtain liquid B; mix 820g deionized water, 72.16g anhydrous ethanol, 0.04g sodium dodecyl sulfate and 0.08g sodium polyoxyethylene fatty alcohol sulfate to obtain liquid C;

[0058] Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 3 h, then allowed to stand for 8 h, centrifuged and washed, and then subjected to hydrothermal reaction at 160 °C for 9 h to obtain polyetheretherketone microspheres;

[0059] (4) Preparation of wear-resistant coating

[0060] The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid were mixed, 2,4,6-trimethylbenzoyldiphenylphosphine oxide was added, nitrogen was introduced and stirred for 20 minutes to obtain the wear-resistant coating.

[0061] Example 3

[0062] A wear-resistant coating, the wear-resistant coating is made of the following raw materials, measured by mass:

[0063] 50 parts of resin prepolymer emulsion, 11 parts of modified nano-spherical alumina, 5 parts of polyetheretherketone microspheres, 0.03 parts of stearic acid, and 0.05 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide;

[0064] The preparation method of the wear-resistant coating is as follows:

[0065] (1) Preparation of resin prepolymer emulsion

[0066] 5.5 g of allyl methacrylate and 1.28 g of butyl acrylate were dissolved in 35.84 g of toluene, 0.06 g of sodium dodecyl sulfate was added, nitrogen was continuously introduced into the device, and then 0.12 g of t-BuP4 and 0.057 g of benzoyl peroxide were added. After reacting at 40° C. for 2.5 h, a mixed solution of hydroquinone and toluene (hydroquinone: toluene=1:10, n / n) was added to terminate the reaction to obtain a resin prepolymer emulsion;

[0067] (2) Preparation of modified nano-spherical alumina

[0068] Dissolve 0.5g of silane coupling agent KH590 in 26g of anhydrous ethanol, adjust the pH value to 4 with 0.5mol / L hydrochloric acid, and react at 40℃ for 30min to obtain liquid A;

[0069] 3.06 g of nano-spherical alumina was added to 67.32 g of liquid A, and the mixture was reacted for 3 h, and then washed with anhydrous ethanol, filtered, and dried to obtain modified nano-spherical alumina;

[0070] (3) Preparation of polyetheretherketone microspheres

[0071] Add 3.28g 1000 mesh polyetheretherketone powder to 39.36mL concentrated sulfuric acid and stir at 45°C for 10h to obtain liquid B; mix 656g deionized water, 82g anhydrous ethanol, 0.08g sodium dodecyl sulfate and 0.12g sodium polyoxyethylene fatty alcohol sulfate to obtain liquid C;

[0072] Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 4 hours, then allowed to stand for 8 hours, centrifuged and washed, and then subjected to hydrothermal reaction at 165°C for 8 hours to obtain polyetheretherketone microspheres;

[0073] (4) Preparation of wear-resistant coating

[0074] The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid were mixed, 2,4,6-trimethylbenzoyldiphenylphosphine oxide was added, nitrogen was introduced and stirred for 15 minutes to obtain the wear-resistant coating.

[0075] Example 4

[0076] A wear-resistant coating, the wear-resistant coating is made of the following raw materials, measured by mass:

[0077] 50 parts of resin prepolymer emulsion, 6 parts of modified nano spherical alumina, 10 parts of polyetheretherketone microspheres, 0.01 parts of stearic acid, and 0.04 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide;

[0078] The preparation method of the wear-resistant coating is as follows:

[0079] (1) Preparation of resin prepolymer emulsion

[0080] 6 g of allyl methacrylate and 1.28 g of butyl acrylate were dissolved in 35 g of toluene, 0.03 g of sodium dodecyl sulfate was added, nitrogen was continuously introduced into the device, and then 0.12 g of t-BuP4 and 0.08 g of benzoyl peroxide were added. After reacting at 45° C. for 3 h, a mixed solution of hydroquinone and toluene (hydroquinone: toluene=1:10, n / n) was added to terminate the reaction to obtain a resin prepolymer emulsion;

[0081] (2) Preparation of modified nano-spherical alumina

[0082] Dissolve 0.5g of silane coupling agent KH590 in 26.5g of anhydrous ethanol, adjust the pH value to 4 with 0.5mol / L hydrochloric acid, and react at 40℃ for 35min to obtain liquid A;

[0083] 3.06 g of nano-spherical alumina was added to 70.38 g of liquid A, and the mixture was reacted for 2 h, and then washed with anhydrous ethanol, filtered, and dried to obtain modified nano-spherical alumina;

[0084] (3) Preparation of polyetheretherketone microspheres

[0085] Add 3.28g 800-mesh polyetheretherketone powder into 32.8mL concentrated sulfuric acid and stir at 50°C for 10h to obtain liquid B; mix 820g deionized water, 82g anhydrous ethanol, 0.06g sodium dodecyl sulfate and 0.1g sodium polyoxyethylene fatty alcohol sulfate to obtain liquid C;

[0086] Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 4 hours, then allowed to stand for 10 hours, centrifuged and washed, and then subjected to hydrothermal reaction at 160°C for 10 hours to obtain polyetheretherketone microspheres;

[0087] (4) Preparation of wear-resistant coating

[0088] The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid were mixed, 2,4,6-trimethylbenzoyldiphenylphosphine oxide was added, nitrogen was introduced and stirred for 20 minutes to obtain the wear-resistant coating.

[0089] Comparative Example 1

[0090] A wear-resistant coating, which is different from Example 1 in that the modified nano spherical alumina is replaced by an equal amount of nano spherical alumina, and the rest is the same as Example 1.

[0091] Comparative Example 2

[0092] A wear-resistant coating is disclosed. The difference from Example 1 is that no modified nano spherical alumina is added in this comparative example, and the rest is the same as Example 1.

[0093] Comparative Example 3

[0094] A wear-resistant coating, which is different from Example 1 in that polyetheretherketone microspheres are not added in this comparative example, and the rest are the same as Example 1.

[0095] The coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were cured under ultraviolet light, and the obtained wear-resistant coatings were tested for relevant properties. The specific results are shown in Table 1.

[0096] The adhesion is tested in accordance with GB / T 9286-1998; the hardness is tested in accordance with GB / T 6739-2006; the impact resistance is tested in accordance with GB / T 1732-2020; and the wear resistance is tested using a BGD-523 paint film abrasion tester (60r / min, 750g, 500r).

[0097] Table 1 Test results

[0098]

[0099] From the comparison of Example 1 with Comparative Examples 1 and 2 in Table 1, it can be seen that the small particle size and smooth surface of the modified nano-spherical alumina enable it to form a tiny rolling or sliding interface in the coating, which helps to reduce the friction coefficient between the coating and the contact surface and reduce wear and tear; the modified nano-spherical alumina particles can act as micro-"balls" to provide lubrication between the coating and the contact surface, thereby reducing friction and wear. At the same time, the high hardness and mechanical strength of the modified nano-spherical alumina can improve the wear resistance of the coating.

[0100] From the comparison between Example 1 and Comparative Example 3 in Table 1, it can be seen that adding polyetheretherketone microspheres to the coating significantly increases the hardness and wear resistance of the coating. The polyetheretherketone microspheres can disperse and resist wear when the coating is rubbed, thereby extending the service life of the coating. The polyetheretherketone microspheres also enhance the impact resistance of the coating to a certain extent. The improvement of these properties enables the coating to maintain good performance even in a more severe use environment. On the other hand, the polyetheretherketone molecules can act as a photoinitiator and work together with 2,4,6-trimethylbenzoyldiphenylphosphine oxide to shorten the curing time of the coating.

[0101] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.

Claims

1. A wear-resistant coating, characterized in that: The wear-resistant coating is made of the following raw materials, in parts by mass: 40-50 parts of resin prepolymer emulsion, 6-11 parts of modified nano-spherical alumina, 5-10 parts of polyetheretherketone microspheres, 0.01-0.03 parts of stearic acid, and 0.03-0.05 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide; The preparation method of the resin prepolymer emulsion comprises the following preparation steps: Allyl methacrylate and butyl acrylate are dissolved in toluene, sodium dodecyl sulfate is added, t-BuP4 and benzoyl peroxide are added under anaerobic conditions, react at 35-45°C for 2-3h, and then a terminator is added to terminate the reaction to obtain a resin prepolymer emulsion; The preparation method of the modified nano spherical alumina comprises the following preparation steps: Dissolve silane coupling agent KH590 in anhydrous ethanol, adjust the pH value to 3-4, and react at 35-40°C for 30-40 minutes to obtain liquid A; Add nano-spherical alumina into liquid A, react for 2-3 hours, wash, filter and dry to obtain modified nano-spherical alumina.

2. The wear-resistant coating according to claim 1, characterized in that: In the preparation method of the resin prepolymer emulsion, the mass ratio of allyl methacrylate:butyl acrylate:toluene is 4-5:1:25-28; the mass ratio of t-BuP4:benzoyl peroxide is 1:0.4-0.7; and the t-BuP4 accounts for 1.5%-1.8% of the total mass of the allyl methacrylate and the butyl acrylate.

3. The wear-resistant coating according to claim 1, characterized in that: In the method for preparing the resin prepolymer emulsion, the terminator is a mixed solution of hydroquinone and toluene.

4. The wear-resistant coating according to claim 1, characterized in that: In the preparation method of the modified nano-spherical alumina, the mass ratio of nano-spherical alumina to liquid A is 1:20-25.

5. The wear-resistant coating according to claim 1, characterized in that: The preparation method of the polyetheretherketone microspheres comprises the following preparation steps: Add polyetheretherketone powder into concentrated sulfuric acid and stir at 45-50°C for 8-10 hours to obtain liquid B; mix deionized water and ethanol to obtain liquid C; Liquid B was slowly added dropwise to liquid C, stirred at room temperature for 3-4 hours, then allowed to stand for 8-10 hours, centrifuged and washed, and then hydrothermally reacted at 155-165° C. for 8-10 hours to obtain polyetheretherketone microspheres.

6. The wear-resistant coating according to claim 5, characterized in that: Polyetheretherketone powder: concentrated sulfuric acid = 1g: 8-12mL.

7. The wear-resistant coating according to claim 5, characterized in that: The particle size of the polyetheretherketone powder is 600-1000 meshes.

8. The method for preparing the wear-resistant coating according to any one of claims 1 to 7, characterized in that: The preparation method of the wear-resistant coating comprises the following preparation steps: The resin prepolymer emulsion, polyetheretherketone microspheres, modified nano-spherical alumina and stearic acid are mixed, and then 2,4,6-trimethylbenzoyldiphenylphosphine oxide is added, and the mixture is stirred for 15-20 minutes under anaerobic conditions to obtain a wear-resistant coating.

Citation Information

Patent Citations

  • Preparation method for reactive polymer containing dangling double bonds

    CN104610484A

  • Water-based acrylate synthetic resin for hub coating and preparation method thereof

    CN108840971A